World economic and social survey 2008 - United Nations.Department of Economic and Social Affairs (New Delhi, 2008)
According to the Survey, economic insecurity arises from the exposure of individuals, communities and countries to adverse events, and from their inability to cope with and recover from the downside losses. Local concerns have been compounded by new global threats as unregulated markets and climate change. The Survey offers a different approach with a strong (3z(Bsocial contract(3y (Band more integrated and pragmatic economic and social policy. It calls for more active policy responses to help communities better manage these new risks, increased investment in preventing threatening events from emerging and more concerted efforts to strengthen the underlying social contracts which are, in the end, the real basis of a more secure, stable and just future. s
Keywords: Economic Survey_world-2008